Diabetes Care for You: leadership, followership, partnership. (2nd February 2023) - Lipscomb, David; Rezazadeh, Eleanor; Rowney, Jane
Abstract: The 2022 Mary MacKinnon lecture reminds us of some of the history of the development of out of hospital specialist diabetes services in the United Kingdom. There have been multiple clarion calls across the years to collaborate, share information and values and break down traditional boundaries in the pursuit of improved patient care and outcomes. Along with this, we note the roles of clinical and managerial leadership, followership and partnership in working together with people living with diabetes to co‐produce a model of diabetes care and then to ensure through good stewardship of shared resources that the expectations of that change are delivered for our population. We go on to discuss how the Diabetes Care for You team has continued to innovate and provide care during the pandemic and conclude with a vision of the future and a challenge for decision makers to put the needs of the population at the forefront of future planning. Copyright © 2023 John Wiley & Sons.